2020
DOI: 10.3390/ijms21165774
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Driven Pathogenesis of Neurotoxicity after Exposure of Cancer Patients to Immune Checkpoint Inhibitors

Abstract: Over the last decade, immune checkpoint inhibitors (ICIs) have revolutionized the treatment of several cancer types. ICIs work through the blockage of immune inhibitory signals, while increasing the T-cell specific immune antitumoral response. However, due to the fact that ICIs’ mechanism of action is not tissue antigen-specific and not limited to the tumor microenvironment, the use of cancer immunotherapy can produce a broad range of immune-related adverse events (irAEs). Neurological immune-related adverse e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 65 publications
(88 reference statements)
0
22
0
Order By: Relevance
“…Cytokines have also been studied as potential prognostic biomarkers in patients treated with ICIs ( Vilariño et al, 2020 ). The elevated expressions of 11 pro-inflammatory cytokines (G-CSF, GM-CSF, fractalkine, FGF-2, IFNa2, IL12p70, IL1a, IL1B, IL1RA, IL2, and IL13) have been correlated with the development of severe irAEs in a cohort of melanoma patients ( Lim et al, 2019 ).…”
Section: Physiopathologymentioning
confidence: 99%
“…Cytokines have also been studied as potential prognostic biomarkers in patients treated with ICIs ( Vilariño et al, 2020 ). The elevated expressions of 11 pro-inflammatory cytokines (G-CSF, GM-CSF, fractalkine, FGF-2, IFNa2, IL12p70, IL1a, IL1B, IL1RA, IL2, and IL13) have been correlated with the development of severe irAEs in a cohort of melanoma patients ( Lim et al, 2019 ).…”
Section: Physiopathologymentioning
confidence: 99%
“…Moreover, the presence of pre-existing subclinical autoimmunity phenomena might contribute to the occurrence of ICI-related immune complications, including nervous complications ( 58 ). The presence of anatomical barriers (such as the blood–brain and blood–nerve barrier), and a different structure of the lymphatic system for the nervous system compared with other organs, could affect the low incidence of ICI-related neurological complications ( 59 ). Neurologic phenomena reversibility seems to be influenced by the different pathogenic mechanisms involved ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Semaphorin 4A is reported to regulate angiogenesis through modulating the VEGF pathway ( Segarra et al, 2012 ), and Ucp2 is a macrophage-specific inducer in response to pulmonary injury ( Wang et al, 2016 ). Besides, many studies have indicated the important roles of an inflammatory response and immune response in cancers ( Vilariño et al, 2020 ) and neurodevelopment ( Tan et al, 2020 ). Among the gene lists of the top 10 most significantly upregulated and downregulated genes interfered by stem cell implantation, NXT2 played pivotal roles in neurodevelopment, whereas Mknk2 , Sema6a , and PIR2 are frequently dysregulated molecules in the pathogenesis of multiple cancer types as evidenced by GeneRIF documented by PubMed.…”
Section: Discussionmentioning
confidence: 99%